Issue Information. Issue 12 (16th November 2017) - Unknown
Abstract : COVER PHOTOGRAPH : Expression of eGFP reporter gene in adult mustn1b:eGFP transgenic zebrafish. A transverse section of the head shows marked eGFP fluorescence in muscle tissue including jaw and cranial muscles, tongue, and heart; From: Promoter architecture and transcriptional regulation of musculoskeletal embryonic nuclear protein 1b (mustn1b) gene in zebrafish ; Paula Suarez‐Bregua, Chien‐ju Chien, Manuel Megias, Shaojun Du, and Josep Rotllant; Developmental Dynamics 246:992–1000.